2020
DOI: 10.1002/adma.202002570
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating 3D Metastructures by Simultaneous Modulation of Flexible Resist Stencils and Basal Molds

Abstract: Metamaterials have gained much attention thanks to their extraordinary and intriguing optical properties beyond natural materials. However, universal high‐resolution fabrications of 3D micro/nanometastructures with high‐resolution remain a challenge. Here, a novel approach to fabricate sophisticated 3D micro/nanostructures with excellent robustness and precise controllability is demonstrated by simultaneously modulating of flexible resist stencils and basal molds. This method allows arbitrary manipulations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…See DOI: https://doi.org/ strategy has been used mainly in certain classes of geometrical design (e.g., tube, polyhedron). 33 In addition, other particular routes, 3D liquid self-shaping strategy 42 or modulating methods based on flexible resist stencil and basal mold, 43 have been reported for patterning and accurately achieving 3D microstructures. However, these techniques have limited control over vital structural parameters and relatively low reliabilities due to frequent collapse and deformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…See DOI: https://doi.org/ strategy has been used mainly in certain classes of geometrical design (e.g., tube, polyhedron). 33 In addition, other particular routes, 3D liquid self-shaping strategy 42 or modulating methods based on flexible resist stencil and basal mold, 43 have been reported for patterning and accurately achieving 3D microstructures. However, these techniques have limited control over vital structural parameters and relatively low reliabilities due to frequent collapse and deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The reason why it is called 3D metamaterials is that their morphology originates from the plastic deformation of a 2D broken structure, which is similar to 3D hollow nanocones, curved bow-ties, and so on. 7,43,44 The formation mechanism results from the structural plastic deformation of the freestanding broken "Γ-shape" metal array, which was fabricated by combining shadow metal-sputtering and following multifilm transfer strategies. These two strategies are as follows: (1) forming partially broken structures in the PMMA hole array by magnetron sputtering shadow deposition; (2) transferring multilayered structures from the silicon wafer with the help of an assistant silver film.…”
Section: Introductionmentioning
confidence: 99%
“…Integration of quantum dots in microring resonators or nanobeam waveguides offers spin-controlled photonic flow, underpinning the essential technique to build nonreciprocal single-photon devices, such as on-chip single-photon isolators and circulators . Alternatively, chiral single photons can be obtained by passing the linearly or elliptically polarized light emitted from a single-photon source through a chiral antenna or metastructural filters (Figure a) . These structural filters acquire chiral selectivities by actuating its three-dimensional (3D) shape to the rotation of the electric field in circularly polarized light, which results in an enhanced response to one specific chirality as compared to the other.…”
mentioning
confidence: 99%
“…In particular, 3D pinwheels can produce a circular dichroism of 0.6 in transmitted infrared light, and 3D spirals are able to polarize the THz beam up to an ellipticity of 28°. Recently, Cai et al reported a fabrication method based on simultaneous modulation of resist stencils and base molds that were applied to fabricate 3D spirals and were able to reduce its dimension to the micron regime with sub-100 nm spatial resolution . This advance extends the working frequency of these patterned chiral filters to the near-infrared and visible regimes where an abundance of quantum emitters exists and can be incorporated for technological development.…”
mentioning
confidence: 99%
See 1 more Smart Citation